Exploring the antecedents of adoption intention of smart healthcare technologies in rehabilitation process - Rodić, Branka; Stevanović, Vladimir; Kljajić, Dragana; Trajkov, Marija; Pecarski, Danijela Pecarski; Filipović, Mila (E-business technologies conference proceedings, 2021)
The introduction of the Internet of Things and wearable technologies in a healthcare enables measurement of the user’s vital parameters. The use of wearable devices in the process of rehabilitation, by doctors or therapists, should enable obtaining information about the psychophysical condition and progress of the patient. By applying the e-health services, the measured data are monitored, stored and analyzed. Based on the analytical results, appropriate methods and biofeedback can be created to improve the implementation of therapy and personalized preventive health messages for users. The main goal of this paper is to examine the antecedents of the adoption of smart healthcare technologies - IoT and wearable computing technology and health services among healthcare employees in the Clinic of rehabilitation Dr Miroslav Zotovic. An integrated adoption model based on TAM and TPB was proposed. The model is planned to be evaluated with about 90 respondents.